The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1002/soej.12427
|View full text |Cite
|
Sign up to set email alerts
|

Financial Incentives and Herding: Evidence from Two Online Experiments

Abstract: Social conformity and information‐based herding have been studied extensively in the social sciences, but there is little experimental evidence on how financial incentives impact the likelihood that an individual will follow the crowd. We present the results of a pair of two‐stage online experiments where we use answers to and confidence about trivia questions—with and without information about the choices of others—to test the impact of financial incentives on an individual's likelihood of engaging in herd be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 24 publications
0
7
1
Order By: Relevance
“…Bhanot and Williamson [ 6 ] conducted online experiments (using Amazon Mechanical Turk) in which 391 participants answered 60 multiple-choice trivia-knowledge questions while the most popular answer was displayed at each question. Correct answers were incentivized randomly with $0, $1, $2 or $3 each in a within-subject design, i.e.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Bhanot and Williamson [ 6 ] conducted online experiments (using Amazon Mechanical Turk) in which 391 participants answered 60 multiple-choice trivia-knowledge questions while the most popular answer was displayed at each question. Correct answers were incentivized randomly with $0, $1, $2 or $3 each in a within-subject design, i.e.…”
Section: Literature Reviewmentioning
confidence: 99%
“…randomized over trials, not over subjects. Bhanot and Williamson [ 6 ] found that monetary incentives increase the proportion of answers that align with the majority. Hence, the studies using incentives yield inconclusive and contradicting results: Particularly, Baron et al [ 5 ] found both an accuracy-increasing and accuracy-decreasing effect of monetary incentives depending on task difficulty.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In these cases, individuals are less likely to rely on their own beliefs and judgments, signifying that, even when the majority’s claim is wrong, an individual may still follow the majority’s opinion. From the 1990s, scholars in the marketing and finance fields invested in this theory (Bhanot & Williamson, 2020 ; Bikhchandani & Sharma, 2000 ; Gong et al, 2022 ; Mowen & Minor, 1995 ; Teng & Liu, 2014 ; Wilkie, 1994 ; Yan et al, 2012 ); however, few studies have been conducted on this topic in the education field. Some results indicated that female adolescents outperform male adolescents in education from the perspective of gender conformity pressure (Egan & Perry, 2001 ; Heyder et al, 2021 ; Vantieghem et al, 2015 ), and Asch ( 1956 ) experimentally found college students showcased conformity behavior in comparing bus routes.…”
Section: Introductionmentioning
confidence: 99%
“…Some results indicated that female adolescents outperform male adolescents in education from the perspective of gender conformity pressure (Egan & Perry, 2001 ; Heyder et al, 2021 ; Vantieghem et al, 2015 ), and Asch ( 1956 ) experimentally found college students showcased conformity behavior in comparing bus routes. Adults are more likely to conform when there are financial incentives to be collected (Bhanot & Williamson, 2020 ); therefore, the incentive for college students to apply for a job or enter graduate school after they obtain a degree may also motivate them to adopt conformity. Thus, exploring what factors will affect college students’ conformity learning behavior is a topic worthy of further study in the field of education.…”
Section: Introductionmentioning
confidence: 99%